2019
DOI: 10.1002/jclp.22787
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the sense of agency: Implications for the psychotherapy of bulimia nervosa‐ A case study

Abstract: A sense of agency is a transtheoretical concept that increases our understanding of important processes in psychotherapy. Agency can be described in terms of how strongly the person believes that she can have an impact on her problematic experiences and behaviors. In this case study, a patient's sense of agency in relation to symptoms of bulimia nervosa was assessed during 3 years of psychotherapy. Five distinct phases of agency in relation to eating disorder symptoms were identified: A false sense of agency o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Presenting agency problems at the onset of therapy is common in patients (Toivonen et al, 2019(Toivonen et al, , 2020, and thus regaining a sense of agency has been identified as a crucial focus in psychotherapy practice (e.g., Lilliengren and Werbart, 2010;Levitt et al, 2016;Wahlström and Seilonen, 2016). When analyzing patient narratives over the course of therapy, a stable increase in agency was found across patient characteristics (e.g., demographics, personality traits), and in various conditions (e.g., Kristmannsdottir et al, 2019). Increase in agency was indeed found to be related to improvement in mental health; moreover, increases in agency occurred prior to improvement in mental health (Adler, 2012).…”
Section: Continuity With Prior Empirical Researchmentioning
confidence: 99%
“…Presenting agency problems at the onset of therapy is common in patients (Toivonen et al, 2019(Toivonen et al, , 2020, and thus regaining a sense of agency has been identified as a crucial focus in psychotherapy practice (e.g., Lilliengren and Werbart, 2010;Levitt et al, 2016;Wahlström and Seilonen, 2016). When analyzing patient narratives over the course of therapy, a stable increase in agency was found across patient characteristics (e.g., demographics, personality traits), and in various conditions (e.g., Kristmannsdottir et al, 2019). Increase in agency was indeed found to be related to improvement in mental health; moreover, increases in agency occurred prior to improvement in mental health (Adler, 2012).…”
Section: Continuity With Prior Empirical Researchmentioning
confidence: 99%
“…Anxiety around readiness for taking this on and excessive worry around motivation to maintain good eating routines was pervasive throughout the transcripts. Kristmannsdottir et al (2019) discuss this idea of agency in their research of people experiencing an ED and claim it is only when a person has a sufficient sense of agency that they can be fully motivated or described as ‘ready for change’. When a person's sense of agency gradually becomes stronger, they can relate to problematic patterns of behaviour in a new way, seeing alternatives and options that are within their means or control agency (Kristmannsdottir et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Particularly interesting were the perceptions of what healthy eating meant to the individuals; it was identified as an assertion of “agency” over their lives. “Agency” can be described as how strongly a person believes s/he can impact on experiences and behaviours and has been suggested to influence success of psychotherapeutic treatment for established ED (Kristmannsdottir et al, 2019 ). Our participants described the development of their eating preferences as an attempt to establish independence from their family's food beliefs and a mechanism to assert control over their lives in times of change (e.g., moving to another country).…”
Section: Discussionmentioning
confidence: 99%